Vulnerable COPD patients with comorbidities: the role of roflumilast - Lipari M; Kale-Pradhan PB (Dove Medical Press, 2014)
Melissa Lipari1,2 Pramodini B Kale-Pradhan1,2 1Department of Pharmacy Practice, Wayne State University; 2St John Hospital and Medical Center, Detroit, MI, USA Abstract: Roflumilast is a selective phosphodiesterase-4 (PDE-4) inhibitor that was approved by the US Food and Drug Administration in February 2011 for the management of chronic obstructive pulmonary disease (COPD). Literature was retrieved through PubMed using the terms “roflumilast” and “COPD”. Reference citations from publications identified were also reviewed. All articles published in English using the terms “roflumilast” and “COPD” were retrieved. For evaluation of clinical efficacy, published Phase III studies and pooled analyses of Phase III trials were included. In seven published Phase III trials, roflumilast at 500 µg daily showed improvements in lung function as measured by pre- and post-bronchodilator forced expiratory volume in 1 second. Roflumilast appears to be useful in vulnerable patients who are at high risk for exacerbations. Roflumilast was found to be effective when administered alone and with concomitant long-acting bronchodilator therapy in the Caucasian and Asian population. Patients with severe-to-very severe COPD, chronic bronchitis, and frequent history of exacerbations derived the greatest benefit with roflumilast. Compared to the standard of care therapies, roflumilast is more cost-prohibitive. Roflumilast was well tolerated, with the most common adverse events observed in clinical trials being diarrhea, nausea, and headache. Weight loss and increased risk of psychiatric events have also been observed with roflumilast in clinical trials. Roflumilast is a safe and effective option for the treatment of COPD. Keywords: roflumilast, COPD, phosphodiesterase-4 inhibitor